REFORMASI BIROKRASI DAERAH ISTIMEWA YOGYAKARTA SEBAGAI IMPLIKASI BUDAYA POLITIK KERATON - Riski Williyanto, Riski (Jurnal Review Politik, 2015)
This article answered questions about the first, The development of political culture palace. Second, the road map of bureaucratic reform. Third, factors supporting and hindering reform of government bureaucracy Yogyakarta. The method based on qualitative descriptive case studies. The results of this study indicate First, the political culture of the palace has been entered in the Government of DIY. Second, the road map of bureaucratic reform adjusted to the Labor Law because of bureaucratic reform DIY Government coincided with the passing of the Labor Law No. 13 of 2012 on Privileges Yogyakarta. So that the arrangement and governance mechanisms based privileges DIY work. Third, The supporting factors, adoption of Act No. 13 of 2012 on privileges Yogyakarta, as well as the existence of the Sultanate and the Duchy. Some government organizations DIY walked less effective because of local laws yet to be passed are Inhibiting factors